Complex Variant of Philadelphia Translocation Involving Chromosomes 9, 12, and 22 in a Case with Chronic Myeloid Leukaemia - F. Malvestiti; C. Agrati; S. Chinetti; A. Di Meco; S. Cirrincione; M. Oggionni; B. Grimi; F. Maggi; G. Simoni; F. R. Grati (Case Reports in Genetics)
Chronic myeloid leukemia (CML) is a hematopoietic stem cell disorder included in the broader diagnostic category of myeloproliferative neoplasms, associated with fusion by BCR gene at chromosome 22q11 to ABL1 gene at chromosome 9q34 with the formation of the Philadelphia (Ph) chromosome. In 2–10% of CML cases, the fusion gene arises in connection with a variant translocation, involving chromosomes 9, 22, and one or more different chromosomes; consequently, the Ph chromosome could be masked within a complex chromosome rearrangement. In cases with variant Ph translocation a deletion on der(9) may be more frequently observed than in cases with the classical one. Herein we describe a novel case of CML with complex variant Ph translocation involving chromosomes 9, 12, and 22. We present the hematologic response and cytogenetic response after Imatinib treatment. We also speculated the mechanism which had originated the chromosome rearrangement.